2000
DOI: 10.1007/3-540-45553-1_23
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Properties of High Redshift and X-ray Selected AGN Samples

Abstract: The NASA/ISO Key Project on active galactic nuclei (AGN) seeks to better understand the broad-band spectral energy distributions (SEDs) of these sources from radio to X-rays, with particular emphasis on infrared properties. The ISO sample includes a wide variety of AGN types and spans a large redshift range. Two subsamples are considered herein: 8 high-redshift (1 < z < 4.7) quasars; and 22 hard X-ray selected sources.The X-ray selected AGN show a wide range of IR continuum shapes, extending to cooler colors t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…ISOPHOT observations of the 2-200 µm SEDs of Seyferts, radio galaxies and QSOs have confirmed these conclusions and improved the quality and spectral detail of the data (Haas et al 1999, Wilkes et al 1999, Rodriguez Espinosa et al 1996, Perez Garcia et al 1998. As part of the European Central Quasar Program (~70 QSOs and radio galaxies) Haas et al (1998aHaas et al ( , 1999 report ISOPHOT/IRAS SEDs, with additional 1.3mm points from the IRAM 30m telescope, for two dozen (mainly radio-quiet) PG QSOs.…”
Section: The Source Of Far-infrared Luminosity In Seyfert Galaxies Anmentioning
confidence: 84%
See 1 more Smart Citation
“…ISOPHOT observations of the 2-200 µm SEDs of Seyferts, radio galaxies and QSOs have confirmed these conclusions and improved the quality and spectral detail of the data (Haas et al 1999, Wilkes et al 1999, Rodriguez Espinosa et al 1996, Perez Garcia et al 1998. As part of the European Central Quasar Program (~70 QSOs and radio galaxies) Haas et al (1998aHaas et al ( , 1999 report ISOPHOT/IRAS SEDs, with additional 1.3mm points from the IRAM 30m telescope, for two dozen (mainly radio-quiet) PG QSOs.…”
Section: The Source Of Far-infrared Luminosity In Seyfert Galaxies Anmentioning
confidence: 84%
“…This finding suggests that the far-IR emission in QSOs is a distinct physical component that may not be physically related to the shorter wavelength emission. Wilkes et al (1999) report the first results of the US Central QSO program that contains another 70 objects and extends to z=4.7. These data confirm as well the presence of thermal dust emission with a wide range of temperatures.…”
Section: The Source Of Far-infrared Luminosity In Seyfert Galaxies Anmentioning
confidence: 99%
“…In hoping to detect more quasars, several groups have carried out mid-and far-infrared photometry using the Infrared Space Observatory (ISO; Kessler et al 1996). The first report of the ISO European Central Quasar Programme which observed 70 quasars between 4.8 and 200 µm including high-redshift quasars has been published by Haas et al (1998), and the ISO/N ASA AGN Key Project has also observed 72 quasars and AGNs covering a range of redshift up to 4.7 (Wilkes et al 1999).…”
Section: Havementioning
confidence: 99%
“…Granato et al 1996;Andreani et al 1999). These models are attractive because of the similar ratios of far-IR to mid-IR fluxes in quasars of widely different luminosities (Haas et al 1998;Wilkes et al 1999). However, they require a large amount of relatively cool dust at large radii (up to ∼ 1 kpc) from the quasar.…”
Section: C 318: a Hyperluminous Infrared Quasarmentioning
confidence: 99%